Citizen science chlorine surveillance during the Flint, Michigan federal water emergency. (1st August 2021) - Roy, Siddhartha; Mosteller, Kaylie; Mosteller, Matthew; Webber, Keri; Webber, Victoria; Webber, Stephanie; Reid, Lola; Walters, LeeAnne; Edwards, Marc A.
Highlights: Two Legionella outbreaks in Flint (2014–15) raised concerns about chlorine residuals. A systemwide citizen campaign in 2018–19 confirmed improving chlorine levels. An inexpensive, reliable color wheel helped expand chlorine surveillance datasets. A decision tree based on citizen chlorine data could be used to help manage Legionella risks. Implications for low water use periods such as the current COVID-19 pandemic are discussed. Abstract: Rising incidence of waterborne diseases including Legionellosis linked to low chlorine residuals in buildings and the availability of inexpensive testing options, create an opportunity for citizen science chorine monitoring to complement sampling done by water utilities. University researchers and Flint residents coordinated a citizen science chlorine surveillance campaign in Flint, Michigan in 2015–19, that helped expose the nature of two deadly Legionnaires Disease outbreaks in 2014–2015 during the Flint Water Crisis and progress of system recovery during the Federal emergency. Results obtained with an inexpensive color wheel were in agreement with a digital colorimeter (R 2 =0.99; p = 2.81 × 10 −21 ) at 15 sites geographically distributed across Flint. Blinded tests revealed good agreement between official ( n = 2051) and citizen ( n = 654) data in terms of determining whether regulatory guidelines for chlorine were met, but a discovery that the citizen data were statistically lower than the city's ( p <0.00001) especially in warm summer months led to recommendations for increased flushing of service lines before measurements. This work suggests that expanded citizen surveillance of chlorine, site specific flushing advice, and guidance on decisions about water heater set point could help consumers reduce Legionella risks in their homes. Citizen science initiatives for chlorine monitoring offer a unique opportunity for mutually beneficial collaborations between consumers and utilities to reduce the main source of waterborne disease in developed countries. Graphical abstract: Image, graphical abstract